The self-reliant entrepreneur : 366 daily meditations to feed your soul and grow your business - Jantsch, John (Wiley, 2019)
"The Self-Reliant Entrepreneur is a unique collection of 366 inspirational meditations for entrepreneurs informed by the curated thoughts and powerful writing of a collection of American authors. It is built on the successful daily devotional model, and is arranged in a calendar format featuring a brief reading from the public domain works of Transcendentalist literature and beyond. The readings are followed by a reflection from the author based on his lifetime of coaching small business and startups that offers entrepreneurial context around such enduring themes as self-awareness, trust, creativity, resilience, failure, growth, freedom, love, integrity, and passion"--